Populations of the stygobiotic amphipod Palearcticarellus pusillus (Martynov, 1930) maintain genetic connectivity between the mountain springs and the deep bottom habitats of Lake Teletskoye (Altai Mountains, Russia) - Marin, Ivan; Yanygina, Liubov; Ostroukhova, Svetlana; Palatov, Dmitry (International journal of speleology, 2024)
The diversity of underground fauna is often associated with the presence of karst areas, which have extensive underground cavities and connecting channels. Non-karst areas, however, make up a larger portion of the planet’ surface, and our understanding of the distribution and dispersal abilities of underground fauna in these areas currently remains limited. During a recent study of the diversity of stygobiotic crustaceans in the mountain streams of the Kurai Mountain Range (Altai, Russia), a small-sized species of crangonyctid amphipod, Palearcticarellus pusillus (Crustacea, Amphipoda, Crangonyctidae) was found in high-altitude springs. This species has been previously known only from deep-water habitats in Lake Teletskoye, and molecular genetic analysis revealed that these amphipods maintain genetic connections between the springs and bottom lake habitats. We assume that individuals of this certainly stygobiotic species fall to the bottom of the lake as a result of leaching from tectonic faults connecting these habitats and are not permanent inhabitants of the lake bottom. This hypothesis also suggests that the very small body size of these animals may be related to the narrow crevices and pores of the tectonic faults, rather than neoteny, as it has been previously suggested. The estimated divergence time calculation has also revealed that P. pusillus obviously diverged from its sister species, Palearcticarellus mikhaili from valley springs in Kurai Steppe, ~5 Ma, at the beginning of the Pliocene, possibly due to the uplifting of the Kurai Mountain Range. Subsequent speciation occurred as a result of secondary tectonic activity and changes in groundwater flow, likely during the Pleistocene, approximately 2.7–0.7 Ma. Populations that were isolated for a long time continue to live near mountain springs in the study area.